Dynamic performance analysis of photovoltaic–thermal solar collector with dual channels for different fluids. (15th July 2016) - Su, Di; Jia, Yuting; Huang, Xiang; Alva, Guruprasad; Tang, Yaojie; Fang, Guiyin
Graphical abstract: The hourly variation of outlet temperature of working fluid. Highlights: The dynamic model of the PV/T collector with dual channels for different fluids was developed. The performance parameters are derived to carry out comparative analyses. The performances of the PV/T collector were evaluated and analyzed. The PV/T configuration and fluid parameters have influences on the performances of the collector. Abstract: The performance of the hybrid photovoltaic (PV) module depends on its operating conditions (especially temperature). Only a small percentage of incoming solar radiation is converted into electricity, and the rest is converted into heat. This overheats the PV module and reduces its performance. This work presents the performance of photovoltaic–thermal (PV/T) solar collector with dual channels for different fluids. The PV/T solar collector's electrical and thermal characteristics like temperatures of the solar cell and outlet fluids, electric power generation efficiency and thermal power efficiency are analyzed through comparison of four PV/T collectors with different fluids. It is found that water–water cooled PV/T collector is the most efficient in both electrical and thermal performance. Water–water cooled PV/T collector can provide the most amount hot water. The temperature of water in air–water case is the highest. Air–air cooled PV/T collector may provide the most amount hot air which its temperature is the highest. It is also found that an increase in mass flow rate of water and the height between the upper pipe and the lower pipe leads to better overall efficiency in water–water cooled PV/T collector.